Adsorption of Pb(II) from glucose solution on thiol-functionalized cellulosic biomass - Wu, Zhimin; Cheng, Zihong; Ma, Wei (Bioresource technology, 2012)
► The glucose solution is used as simulative drinks in Pb(II) adsorption on thiol-functionalized absorbent cotton. ► There was no loss of glucose during the adsorption process. ► The increase of initial glucose concentrations makes contribution to Pb(II) adsorption. ► The modified cellulosic biomass with more effective groups presents greater adsorption capacity. ► The modified cellulosic biomass may be a promising adsorbent for heavy metal ions removal in beverage industry. Absorbent cotton, wood sawdust, buckwheat hull were thiol-functionalized to facilitate selective adsorption of Pb(II) from glucose solution. Fourier transform infrared (FTIR) spectroscopic analysis confirmed the formation of S–H modifications. While unmodified absorbent cotton had a Pb(II) adsorption capacity of 10.78mg/g, thiol-modified absorbent cotton was able to adsorb 28.67mg/g at optimum pH 6.0. The Pb(II) adsorption capacity increased as the concentration of Pb(II) or glucose increased without loss of glucose during the adsorption process. Wood sawdust and buckwheat hull exhibited greater Pb(II) uptake both before and after modification (wood sawdust: 17.03mg/g and 43.14mg/g, buckwheat hull: 34.06mg/g and 44.84mg/g), because these cellulosic biomass contained more helpful functional groups for metal binding. The results suggested that modified cellulosic biomass might be a promising adsorbent for heavy metal ion uptake in beverage industry.